Stress-associated weight gain, fibromyalgia symptoms, cardiometabolic markers, and human growth hormone suppression respond to an amino acid supplement blend: Results of a prospective, cohort study - Pekarovics, Susan; Beres, Adam; Kelly, Colleen; Billes, Sonja K.; Heaton, Amy L. (Frontiers in Endocrinology, 2023)
An orally administered amino acid-based test supplement was recently shown to increase human growth hormone (hGH) in healthy adults. This prospective, observational, single-center, single-arm cohort study investigated the effects of 24 weeks of daily oral administration of the test supplement in individuals with stress-related weight gain, fibromyalgia and stress-related low-normal hGH production (15-30th percentile for age-appropriate levels) on insulin-like growth factor 1 (IGF-1), an indicator of hGH levels caused by stress related stimulation of somatostatin. Participants continued to receive standard care. The primary endpoint was the change from baseline to endpoint (Week 24) in serum IGF-1. Additional endpoints included the change in body weight, clinical symptoms (assessed with the Revised Fibromyalgia Impact Questionnaire [FIQR], range 0-100, and Perceived Stress Scale [PSS], range 0-40), fasting cardiometabolic markers, tolerability, and safety. The study enrolled 84 fibromyalgia patients with low-normal age-adjusted IGF-1 serum levels. High mean ± SD baseline FIQR and PSS scores of 76±16 and 32±5, respectively, indicated poor to moderate symptom management with standard care. All individuals completed 24 weeks. Serum IGF-1 levels increased with a Week 24 mean±SE change of 28.4±3.0 ng/mL (p<0.001). Body weight was reduced with a Week 24 mean ± SE change of -5.5 ± 0.3 kg (p<0.001) (a 6.5% weight loss from baseline). The change from baseline in FIQR and PSS scores were -29.1±1.1 and -20.0±0.8, respectively (both p<0.001), indicating a substantial improvement. Statistically significant improvements from baseline to Week 24 were observed in systolic and diastolic blood pressure, HbA1c, LDL and HDL cholesterol, and triglycerides (all p<0.001). The supplement was well tolerated; no adverse events were reported. Sustained augmentation of IGF-1 with the test supplement may represent a unique method of improving clinical symptoms, including stress-related weight gain, in individuals with fibromyalgia and stress-associated low-normal hGH.